Personnel training processes at hotels affiliated with COTELCO in the city of Villavicencio, (Meta) Erickson Mayorga - Rocio Hortua (GEON Journal (Management, Organizations and Business), 2015)
Staff training is a vital issue for organizations today as when implementing a structured training plan can be achieved by strengthening human talent within the organization, therefore it is appropriate to conduct an assessment of the processes of training of personnel in COTELCO affiliated hotels in the city of Villavicencio to know how is handling this issue in a representative sector of the region . This diagnostic displays the general characteristics of the training process, the effects of applying them and makes proposals and strategies to generate indicators of improvement in the sector.
Keywords: Training; Diagnosis; COTELCO; Hotels and Strategies